Anchor shape gap coupled patch antenna for WiMAX and WLAN applications. Issue 1 (24th January 2019) - Singh, Vivek; Mishra, Brijesh; Singh, Rajeev
Abstract : Purpose: Purpose of this study is to design a compact gap coupled anchor shape patch antenna for wireless local area network/high performance radio local area network and worldwide interoperability for microwave access applications. Design/methodology/approach: An anchor shape microstrip antenna is conceived, designed, simulated and measured. The anchor shape antenna is transformed to its rectangular equivalent by conserving the patch area. Modeling and simulation of the antenna is performed by Ansys high frequency structure simulator (HFSS) electromagnetic solver based on the concept of finite element method. The simulated results are experimentally verified by using Agilent E5071C vector network analyzer. Theoretical analysis of an electromagnetically gap coupled anchor shape microstrip patch antenna has been performed by obtaining the lumped element equivalent of the transformed antenna. Findings: The proposed antenna has a compact conducting patch of dimension 0.26 λ × 0.12 λ mm 2 ( λ is calculated at lower resonating frequency of 3.56 GHz) with impedance bandwidths of 100 and 140 MHz and antenna gains of 1.91 and 3.04 dB at lower resonating frequency of 3.56 GHz and upper resonating frequency of 5.4 GHz, with omni-directional radiation pattern. Originality/value: In literature, one does not encounter anchor shape antenna using the concept of gap coupling and parasitic patches. The design has been optimized for wireless local area network/worldwide interoperability for microwave access applications with a relatively low patch area (291.12 mm 2 ) as compared to other reported antennas for wireless local area network/worldwide interoperability for microwave access applications. Transformed antenna and the actual experimental antenna behavior varies, but the resonant frequencies of the transformed antenna as observed by theoretical analysis and simulated results (by high frequency structure simulator) are reasonably close, and the percentage difference between the resonant frequencies (both at lower and upper bands) is within the permissible limit of 1-2.5 per cent. Results confirm the theoretical proposition of transformation of shapes in antenna design, which allows a designer to adapt the design shape according to the application.